2005
DOI: 10.5194/acpd-5-13053-2005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ion concentrations of PM<sub>10–2.5</sub> and PM<sub>2.5</sub> aerosols over the eastern Mediterranean region: seasonal variation and source identification

Abstract: Abstract. The annual averages of particulate matters (PM10, PM10–2.5 (coarse) and PM2.5 (fine)) in a densely populated area of Beirut were measured and found to be 84±27, 53±20 and 31±9 μg m−3, respectively. Ion Chromatography (IC) analysis of the collected PM Teflon filters showed that NaCl, CaSO4 and Ca(NO3)2 were predominant in the coarse particles, while (NH4)2SO4 was the main salt in the fine particles. Using the non destructive Fourier Transform Infra Red-Attenuated Total Reflection (FTIR-ATR) technique,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…12 that NO Ϫ 3 , SO 2Ϫ 4 , and Ca 2ϩ are the main ion components: their mass represents 89% of the total ion mass. In addition, we note that SO 2Ϫ 4 is the main ion component of fine-mode particles, in accordance to previous studies (Kouyoumdjian and Saliba 2005) and that its level (6.4 g m Ϫ3 ) is comparables to the SO 2Ϫ 4 levels reported for coastal sites of the central-eastern Mediterranean (e.g., Bardouki et al 2003). The latter results show the significant contribution of sulfates and nitrates to the fine fraction of the aerosol load even during a dust event in accordance to SEM analyses on impactor filters (Fig.…”
Section: E Ion Chromatography Analyses On the Pm25 Sample: Methodolsupporting
confidence: 93%
See 1 more Smart Citation
“…12 that NO Ϫ 3 , SO 2Ϫ 4 , and Ca 2ϩ are the main ion components: their mass represents 89% of the total ion mass. In addition, we note that SO 2Ϫ 4 is the main ion component of fine-mode particles, in accordance to previous studies (Kouyoumdjian and Saliba 2005) and that its level (6.4 g m Ϫ3 ) is comparables to the SO 2Ϫ 4 levels reported for coastal sites of the central-eastern Mediterranean (e.g., Bardouki et al 2003). The latter results show the significant contribution of sulfates and nitrates to the fine fraction of the aerosol load even during a dust event in accordance to SEM analyses on impactor filters (Fig.…”
Section: E Ion Chromatography Analyses On the Pm25 Sample: Methodolsupporting
confidence: 93%
“…We believe that the rather high mass concentrations of K ϩ , Mg 2ϩ , and Ca 2ϩ reported in Table 3, are due to the Saharan dust particles collected on 30 June, being K ϩ , Mg 2ϩ , and Ca 2ϩ elements of illite/smectite and dolo- mite particles. In fact, Kouyoumdjian and Saliba (2005) have found in PM2.5 samples collected over the eastern Mediterranean, annual mean concentrations of 0.08, 0.03, and 0.52 g m Ϫ3 for K ϩ , Mg 2ϩ , and Ca 2ϩ , respectively. In contrast, we have found mass concentrations of 0.29, 0.28, and 2.5 g m Ϫ3 for K ϩ , Mg 2ϩ , and Ca 2ϩ , respectively.…”
Section: E Ion Chromatography Analyses On the Pm25 Sample: Methodolmentioning
confidence: 96%
“…In this study, the average ratio of NO 3 − /SO 4 2− was 0.28 ± 0.12 and 0.44 ± 0.33 in fine and coarse particles, indicating a greater contribution of SO 4 2− that shows the dominance of stationary sources compared to vehicular activity. Earlier studies reported a high average NO 3 − /SO 4 2− ratio in cities such as Bobadela (Almeida et al 2005), Rio de Janeiro (Mariani and de Mello 2007) and Beirut (Kouyoumdjian and Saliba 2005) ( Table 2).…”
Section: Secondary Inorganic Aerosolmentioning
confidence: 88%
“…Figure 5). Secondary particles that are mainly ammonium sulfate and nitrate formed in the air from regional or local gaseous emissions of sulfur dioxide and oxides of nitrogen reacting with ammonia [55]. SO 4…”
Section: Ff-related Ftir Spectral Featuresmentioning
confidence: 99%